DISEMINASI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DALAM PENINGKATAN KESADARAN HUKUM MASYARAKAT DI DESA SIDETAPA TERKAIT URGENSI PENCATATAN PERKAWINAN UNTUK MEMPEROLEH AKTA PERKAWINAN - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Jurnal Pengabdian Kepada Masyarakat Media Ganesha FHIS, 2022)
Marriage does not only unite a man and a woman in a house/family. Marriage always carries legal consequences for the wife and husband who are legally married. Based on the legal requirements of a marriage above, we can see that the validity of a marriage according to the Marriage Law is based on the religious laws and beliefs of each. However, all events that occur in the family that have legal aspects need to be recorded and recorded, so that both the person concerned and other interested parties have an authentic deed regarding the event. Thus, the legal position of a person becomes clear and firm. If we look at the consequences of not having a marriage certificate as authentic proof in a marriage, then we can say that a marriage certificate has a very important role/meaning in household life. In accordance with the focus of the problem and the purpose of this activity, the method used in carrying out this activity is the method of dissemination and internalization to members of the public with a ball pick-up system. This activity is a terminal activity in order to increase the knowledge and insight of the people of Sidetapa Village in understanding legal regulations and legal awareness of the regulations governing the registration of marriages (Marriage Law) in order to obtain a marriage certificate. In its implementation, this activity refers to a synergistic pattern between experts and practitioners from the Ganesha University of Education and related agencies, namely the Office of Population and Civil Registration. On the other hand, this program is directed at creating a collaborative and democratic climate of cooperation between the world of higher education and society at large under the coordination of related agencies. As for the things that were achieved in the implementation of this Community Service in an effort to increase the legal awareness of the people of Sidetapa village regarding the urgency of registering marriages to obtain a marriage certificate, namely: a. There has been a positive change in the knowledge regarding public awareness in terms of the correct procedures for registering marriages. b. There has been a positive change in the knowledge of the village community in general and youth in particular about the importance of marriage certificates and they have begun to register marriages in an orderly manner, by seeking more in-depth information on the process of registering marriages.